PENGGUNAAN ALUR ELIPS PADA SKENARIO PROGRAM FILM TELEVISI “KOTAK HITAM ARTA” - Ervindha Pramudya Rani (Saraswati)
Now days, in Indonesia, there are so many television movie which is broadcasted in Indonesian television. Arranging the scenario with a story about family can add different types of stories in television movie. A Family life can be inspired by a television program for example, the lack of parenta control to the children while they are watching television. The nature of children, aged 10 is still in the category of the end of the childhood period.  By looking and hearing what they have got, they believe it easily. The Scenario tells about the lack of parental supervision to the children who like watching television. Parental supervision at the end of childhood is needed to form the character of the children itself. Without parental supervision, the children can be easily affected by the attitude, words and perception from the television progrmas they are watching. Telling the scenario using the elliptical plot that makes the first scene location is also the final scene location. Explaining about the impact of television to the children who get less parental supervision is expected can be used as an overview of the impact of television to the children character because of the  lack of parental supervision. So the parents can pay more attention to the children when they are watching television. Using elliptical plot makes the story become more varied because it is not presented in a normal way.  The use of flash back and unclear part of the story at the beginning can cause the audience wait the end of the story. Keywords: Scenario, elliptical, television movie, kid.